Year of fire, year of ash the Soweto school children's revolt that shook apartheid - Hirson, Baruch (London Zed Books, 2016)
Originally banned on publication by the apartheid government, Year of Fire, Year of Ash is an eye-opening account of how, in June 1976, 20,000 school students faced down the tanks and guns of a vicious racist regime, in a revolt that galvanized the black working-class and became a pivotal turning point for the anti-apartheid movement. More than this, the book overturns much of the conventional logic that served to explain the event at the time, showing it was not simply a student protest, but part of a wider uprising.
Includes index
Keywords: South Africa -- History -- Soweto Uprising, 1976; South Africa -- Politics and government -- 1978-1989